2005
DOI: 10.1002/glia.20223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokines on microglial phenotypes and astroglial coupling in an inflammatory coculture model

Abstract: Cytokines play an important role in the onset, regulation, and propagation of immune and inflammatory responses within the central nervous system (CNS). The main source of cytokines in the CNS are microglial cells. Under inflammatory conditions, microglial cells are capable of producing pro- and antiinflammatory cytokines, which convey essential impact on the glial and neuronal environment. One paramount functional feature of astrocytes is their ability to form a functionally coupled syncytium. The structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 72 publications
6
78
1
1
Order By: Relevance
“…As CXCL12 is expressed in high levels in the normal CNS, it is more logical that it would exert anti-inflammatory effects under normal circumstances. Consistent with this possibility, we found that AMD3100-treated mice had significantly increased levels of IFN-␥, decreased levels of IL-10, and increased levels of cytokines and chemokines associated with monocyte and microglial activation, including TNF-␣ and CXCL10 (72,73), indicating that CXCR4 activation is antiinflammatory in the spinal cord. Others have reported that CXCR4 expression by cells of myeloid lineage is dynamic and regulated by the activation state of the cell (74,75).…”
Section: Discussionsupporting
confidence: 74%
“…As CXCL12 is expressed in high levels in the normal CNS, it is more logical that it would exert anti-inflammatory effects under normal circumstances. Consistent with this possibility, we found that AMD3100-treated mice had significantly increased levels of IFN-␥, decreased levels of IL-10, and increased levels of cytokines and chemokines associated with monocyte and microglial activation, including TNF-␣ and CXCL10 (72,73), indicating that CXCR4 activation is antiinflammatory in the spinal cord. Others have reported that CXCR4 expression by cells of myeloid lineage is dynamic and regulated by the activation state of the cell (74,75).…”
Section: Discussionsupporting
confidence: 74%
“…This contrasts with previous findings that Cx26 and Cx43 expression down-regulated MCP-1 levels in glioblastoma cells, leading to suppressed growth (41), and may suggest some cell type differences. Similarly, there have been many reports positively correlating expression levels of IL-6 and connexins as a part of the inflammatory response (42)(43)(44)(45); however, these all propose IL-6-mediated up-regulation of connexins rather than the connexin-mediated regulation of IL-6 as seen in this study. Our results indicate that not all proangiogenic or antiangiogenic molecules are regulated in synergy, which highlights the complexity of connexin-mediated pathways that likely are involved in cell growth and differentiation under various stimuli and in distinct cell types.…”
Section: Discussionmentioning
confidence: 41%
“…2). We reasoned that because TNF is a potent activator of microglia (Aggarwal et al, 2000;Hinkerohe et al, 2005) and a known mediator of LPS action in peripheral tissues (Beutler, 2005), chronic infusion of DN-TNFs to block solTNF signaling during an inflammatory stimulus might prevent TH-positive cell loss in the SNpc of LPS-infused rats. Unbiased stereological measurements of TH-IR/NeuN neuron soma and fluorescence densitometry of TH-positive fiber density revealed that coinfusion of XENP345 (70 ng/h) with LPS (5 ng/h) for 14 d into rat substantia nigra rescued ϳ50% of the LPS-induced nigrostriatal degeneration measured 8 weeks after the start of infusion (Fig.…”
Section: Resultsmentioning
confidence: 99%